C-groups of high rank for the symmetric groups - Fernandes, Maria Elisa (2019)
We give presentations for the C-groups of rank n – 1 of the symmetric group Sn. We also classify C-groups of rank n – 2 for Sn. We show that all these C-groups correspond to regular hypertopes, that is, thin, residually connected flag-transitive geometries. Therefore we generalise some similar results obtained in the framework of string C-groups that are in one-to-one correspondence with abstract regular polytopes.